Taking the steps toward sustainable livestock: Our multidisciplinary global farm platform journey - Rivero, M.J.; Evans, A.C.O.; Berndt, Alexandre; Cartmill, A.; Dowsey, A.; Farruggia, A.; Mignolet, C.; Enriquez-Hidalgo, D.; Chadwick, David R.; McCracken, D.I.; Busch, D.; Pereyra, F.; et al. (Oxford University Press, 2021)
Implications • The Global Farm Platform was conceived and established to explore multidisciplinary strategies for optimising the sustainability of ruminant systems around the world. • International sustainability issues are common, but the solutions are often region-specific; therefore, our farms, situated across all major agroclimatic zones, are a unique resource worldwide. • Each farm is following steps to sustainable livestock to improve their production system(s), thereby developing robust metrics to progress economic, environmental and social viability. • The consortium works collaboratively to improve the sustainability of ruminants, which we argue are a vital component of global food systems, delivering both human and planetary health.